1995
DOI: 10.1037/0022-3514.69.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Reward allocation in task-performing groups.

Abstract: Three situational variables were varied to assess the relative weight given to equity and equality principles in reward allocations in task-performing groups: (a) the functional relation between individual and group performance (additive, conjunctive, or disjunctive), (b) the amount of variation among performances of individual members, and (c) the purpose of the allocation. In 2 studies, participants were asked to allocate rewards among 3 performers in a hypothetical situation; in a third study, participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…To understand which group contexts are most influenced either positively or negatively by the collectivistic blurring of a group's diversity, we build upon Bell's (2007) suggestion to examine the intersection between tasks -whether they are more conjunctive or disjunctive (LePine et al 1997, Steiner 1972) -and diversity type -in which we differentiate between relations-and task-oriented diversity (Jackson et al 1995). Specifically, we propose that, to be successful on conjunctive group tasks (tasks on which all members of the group must complete the task and the group cannot proceed to the next task until each member has done so; Frank and Anderson 1971), groups depend upon a strong sense of solidarity among members (Goncalo et al 2010, Miller andKomorita 1995). In such settings, cohesion is essential, and perceiving relations-based differences among group members (such as national differences, which are typically less task-relevant) may particularly impede the solidarity needed to perform well (Williams and O'Reilly 1998).…”
Section: Group Performancementioning
confidence: 99%
See 1 more Smart Citation
“…To understand which group contexts are most influenced either positively or negatively by the collectivistic blurring of a group's diversity, we build upon Bell's (2007) suggestion to examine the intersection between tasks -whether they are more conjunctive or disjunctive (LePine et al 1997, Steiner 1972) -and diversity type -in which we differentiate between relations-and task-oriented diversity (Jackson et al 1995). Specifically, we propose that, to be successful on conjunctive group tasks (tasks on which all members of the group must complete the task and the group cannot proceed to the next task until each member has done so; Frank and Anderson 1971), groups depend upon a strong sense of solidarity among members (Goncalo et al 2010, Miller andKomorita 1995). In such settings, cohesion is essential, and perceiving relations-based differences among group members (such as national differences, which are typically less task-relevant) may particularly impede the solidarity needed to perform well (Williams and O'Reilly 1998).…”
Section: Group Performancementioning
confidence: 99%
“…Conjunctive tasks require groups to interact to ensure that all members accomplish group goals, as performance is determined by the worst performing members, who can prevent the entire group from completing the group task (Steiner 1972). As such, conjunctive task performance may be particularly derailed by perceived relational differences in groups, which threaten to undermine the group focus, cohesion, and solidarity (Jehn et al 1999) that motivates members to assist, improve, and bring along the weakest performers (Miller and Komorita 1995). Accomplishing disjunctive tasks, in contrast, requires that the most expert members have a greater say in the group's approach, as group performance is determined by the best performing group member (Littlepage 1991).…”
Section: Influences Group Performancementioning
confidence: 99%
“…Miller and Komorita (1995) manipulated the functional relation between individual and group performance. They found that when the performance of a single member is critical for the success of the group, a disproportionate share of the group reward is given to the best performer, and equity is violated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when judging the fairness of distributions or when allocating resources among third parties, people from many societies consider the amount of work contributed toward resource production and prefer equitable distributions (Fischer & Smith, 2003;Marshall, Swift, Routh, & Burgoyne, 1999). When sharing rewards for work with a coworker, people will often try to restore equity by redistributing resources in proportion to work contribution even when doing so means that they receive the smaller share (Almås, Cappelen, Sørensen, & Tungodden, 2010;Frohlich, Oppenheimer, & Kurki, 2004;Miller & Komorita, 1995;Oxoby & Spraggon, 2008).…”
Section: Research Articlementioning
confidence: 99%